Approximate controllability of nonautonomous nonlocal delay differential equations with deviating arguments - Rajib Haloi (Electronic Journal of Differential Equations, 2017)
The objective of this article is to prove sufficient conditions for the approximate controllability for a class of nonautonomous nonlocal finite delay differential equations with deviating arguments in a Hilbert space. We also establish sufficient conditions for the existence of mild solutions. The results are established using the fixed point theorem of Krasnoselskii and theory of semigroup of bounded linear operators. We discuss an example for the application of the analytical results.